2022
DOI: 10.21608/tsnj.2022.255379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implementing a Protocol of Nursing Care on Clinical Outcomes for Patients Undergoing Lumbar Spine Disc Prolapse Surgeries

Abstract: Background: Disc surgeries have seen a remarkable increase in the recent times that requires a prompt intervention of the nursing personnel to maintain the patients' quality of life and return to their normal life. Aim of the study: Evaluate the effect of implementing a protocol of nursing care on clinical outcomes for patients undergoing lumbar spine disc prolapse surgeries. Design and Setting: A quasi-experimental research design was used to collect data from neurosurgery departments at Main Tanta university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, El-seadi etal (40) who reported that, regarding to the control group, there was no statistical significant difference regarding levels of (ODI) at the 2nd and 3rd week post routine hospital care. Comparing to, the study group that there was a high statistically significant improvement regarding levels of (ODI) at the 2 nd and 3 rd week post protocol of nursing care.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, El-seadi etal (40) who reported that, regarding to the control group, there was no statistical significant difference regarding levels of (ODI) at the 2nd and 3rd week post routine hospital care. Comparing to, the study group that there was a high statistically significant improvement regarding levels of (ODI) at the 2 nd and 3 rd week post protocol of nursing care.…”
Section: Discussionmentioning
confidence: 93%
“…Epi info 7 was used to estimate the sample size using the following parameters: • Population size is 192 patients per year (According to the above-mentioned settings records in 2021). This tool was developed by the researcher after reviewing the relevant literature (8,12,18) . It was consisted of two parts:…”
Section: Subjectsmentioning
confidence: 99%
“…Providing patient with adequate knowledge about disease process and treatment modalities through educational programs contributes to an accurate understanding of the disease, this promotes adherence to a healthy behavior, lifestyle modification and regular follow up program. (12) Nurses play an important role in teaching patients about proper self-care activities, wound care, preventive measures of complications, Additionally, nurses help the patient get ready for the rehabilitation phase, which includes instructions for proper positions post operation, postoperative exercises the patient would perform to keep the spine in its neutral posture, discharge instructions and follow up. Nurse assists the patients to adjust with their disease, as well as restoration of function within the family, community, and work.…”
mentioning
confidence: 99%